Indigenous environmental defenders in Aotearoa New Zealand: Ihumātao and Ōroua River. (June 2022) - Mika, Jason Paul; Dell, Kiri; Elers, Christine; Dutta, Mohan; Tong, Qing
This article theorises the question—what is the role and nature of Indigenous environmental defenders in Aotearoa New Zealand? We explore Māori—the Indigenous people of Aotearoa New Zealand—who act as environmental defenders of their lands and waters despite the perpetual insecurity of their constitutional rights and imbalances in power and resources compared with state and corporate actors. The environmental defence of Aotearoa New Zealand by Māori began with the arrival of European explorers' intent on overturning Indigenous institutions of environmental management that has sustained their peoples for a thousand years. Stemming from case study analysis of Māori environmental defenders at Ihumātao in Māngere and Ōroua River in Manawatū, we propose whenua (land) resilience theory to explain the concomitance of environmental defence and development from an Indigenous perspective.